The Effect of Numbered Head Together (NHT) in a Flipped Classroom Environment on Students’ Self-Efficacy and Achievement on Colloid Topics - Melati Melati; Tritiyatma Hadinugrahaningsih (Scientia Publica Media, 2024)
This study aim to determine the effect of the implementation of flipped classroom model integrated Numbered Head Together (NHT) on self efficacy and learning achievement on colloid topics. This method used is quasi experiment with non-equivalent control group design. The sampling technique used is convenient sampling where class XI MIPA 1 is the experimental group and class XI MIPA 3 is the control group. The experimental group was carried out by applying the flipped classroom model integrated Numbered Head Together (NHT) while the control group applied traditional learning. Student self-efficacy was measured using a self-efficacy questionnaire while student learning achievement was measured using a learning achievement test. Hypothesis test of learning achievement test and self-efficacy questionnaire using t-test. The results of the independent t-test on the posttest value showed that the average posttest value of the experimental group was higher than the control group. Hypothesis testing of the self-efficacy questionnaire with independent t-test on the post-questionnaire showed the level of self-efficacy in the experimental group after being given treatment, higher than the control group. The conclusion of this study is that the application of the flipped classroom model integrated Numbered Head Together (NHT) can improve self-efficacy and student learning achievement on colloid topics.